Transplant-associated thrombotic microangiopathy in pediatrics: incidence, risk factors, therapeutic options, and outcome based on data from a single center - Kafa, Kinan; Hoell, Jessica I. (Frontiers in Oncology, 2024)
Background: Transplant-associated thrombotic microangiopathy (TA-TMA) is a critical complication of hematopoietic stem cell transplantation. Awareness about TA-TMA has increased in recent years, resulting in the implementation of TA-TMA screening in most centers.Methods: Retrospective analysis of children who underwent autologous or allogeneic hematopoietic stem cell transplantation at our center between January 2018 and December 2022 was conducted to evaluate the incidence, clinical features, and outcomes of TA-TMA following the administration of different therapeutic options.Results: Forty-five patients comprised the study cohort, of which 10 developed TA-TMA with a cumulative incidence of 22% by 100 days after transplantation. Patients with and without TA-TMA in our cohort displayed an overall survival of 80% and 88%, respectively, (P=0.48) and non-relapse mortality of 0% and 5.7%, respectively, (P=0.12) at one year after transplantation. Risk factors for TA-TMA development included allogeneic transplantation and total body irradiationbased conditioning regime. Among the 10 patients with TA-TMA, 7 did not meet the high-risk criteria described by Jodele and colleagues. Of these 7 patients, 2 responded to calcineurin-inhibitor withdrawal without further therapy and 5 developed multiorgan dysfunction syndrome, were treated with anti-inflammatory steroids (prednisone), and all responded to therapy. The three high-risk TA-TMA patients were treated with complement blockade or prednisone, and all responded to therapy.TA-TMA is a multifactorial complication with high morbidity rates. Patients with high-risk TA-TMA may benefit from complement blockade using eculizumab. No consensus has been reached regarding therapy for patients who do not meet high-risk criteria. Our analysis showed that these patients may respond to anti-inflammatory treatment with prednisone.